Design of Cities at the time of resilience and climate change. Experiments in Rome and Puerto Rico looking at Africa (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2018)
This paper collects design experiments elaborated in professional and in the teaching activity which have been developed on case studies in Sudan, Italy and Puerto Rico. They propose comparable design solutions for different condition in scale, geography and climate. At least, they try to define design methodologies useful in other design contexts with similar economic conditions. This paper represent a preliminary reflection which deserves further and more extended analysis.Â